THE USE OF STUDENTS TEAMS-ACHIEVEMENT DIVISION (STAD) TO IMPROVE READING COMPREHENSION ON REPORT TEXT (A Classroom Action Research at Eighth Grade Students) - Nurhuda Nurhuda (ICoTE Proceedings)
This study is aimed to improve students’ reading comprehension through the use of Student Teams-Achievement Division (STAD). Students at VIIIA grade students have difficulty to comprehend reading materials especially on report text. Most of them often fail in reading comprehension tests caused by the lack of language mastery. Therefore, their achievements do not achieve the minimal score. The important of written test is not avoided. It is one of learning measurement tools in educational setting. Student Teams-Achievement Division (STAD) is chosen to solve this problem. STAD is one of cooperative learning provides a chance for students to learn, share, exchange, and assist each student to reach group goals. The social value of STAD as cooperative learning allows students to help each other improve a student learning achievement and others during teaching and learning process. This study is a classroom action research. The data will be collected through test for measuring reading comprehension, observation checklist, field note and interview. The finding is expected that the teaching technique effective to improve reading comprehension.